Gestion par projets et risques pour la santé psychologique au travail dans la nouvelle économie - Marie-Josée Legault; Hind Belarbi-Basbous (Perspectives Interdisciplinaires sur le Travail et la Santé)
Are there distinct mental health problems among workers in the new economy? Although we may observe that the psychological demand - decision latitude model of Karakek and Theorell is appropriate and also finds its application in this type of workplace, we also notice some particular forms that these factors take in the management-by-project work organization model. Akin to the so-called "client’s hyper-demanding activity" as identified by Christophe Dejours, these forms were observed during a recent field study about balancing work and family in seven Montreal organizations. The qualitative study collected data from 88 individual interviews of information technology engineers, evenly distributed by gender. These observations allow a nuance of the above-mentioned theoretical mental health model to be considered, to take into account the deleterious effects of a very broad decision latitude combined with huge responsibilities among highly qualified workers.